THE DISCOVERY OF EARLY ORDOVICIAN OPHIOLITE MÉLANGE IN TAERBAHATAI MTS., XINJIANG, NW CHINA - Zhu Y.F.; Xu X. (My University, 2006)
We report a discovery of an ophiolite mélange in Taerbahatai Mts. (Xinjiang, NW China), which underlies the Early Carboniferous Heishantou Group consisting mainly of mudstone, siltstone, tuff, alloclastic rocks, volcanic breccia and lava. The breccia includes serpentite, gabbro, basaltic trachyandesite, trachyte, and silicalite. The Ophiolite mélange consisting of altered gabbro, serpentine peridotite, and silicalite occurs on the bottom of this volcanic stratum. Peridotite has undergone strong serpentinization and was completely replaced by serpentinite, but the pseudomorph of olivine and orthopyroxene still are preserved. Volcanism obviously postdated the emplacements of the Ophiolite mélange, and the eruption was strong as large gabbro and other breccia are frequently observed. Clinopyroxene grains in the altered gabbro from the bottom of the Ophiolite mélange are relatively fresh and show a kind of exsolution texture (whilst all plagioclase grains were replaced by hydrogrossular showing pseudomorph of plagioclase). All the exsolution lamellae are brown spinel. The spinel lamellae (or leafs) are parallel to each other. Zircon separated from this altered gabbro is dated to be 478.3 ± 3.3Ma (MSWD = 1.09, n = 14) by SHRIMP method. This age represents the emplacement time of the Taerbahatai Ophiolite mélange during the Early Ordovician epoch.
Keywords: ALTERED GABBRO; CLINOPYROXENE; EARLY ORDOVICIAN EPOCH; OPHIOLITE MÉLANGE; SHRIMP CHRONOLOGY; SPINEL EXSOLUTION; TAERBAHATAI MTS.; XINJIANG; Carboniferous; Ordovician; Paleozoic::Carboniferous; Палеозой::Каменноугольная; Paleozoic::Ordovician; Палеозой::Ордовикская